CONFIDENCE ANALYSIS AND CALIBRATION OF A FC-28 SOIL MOISTURE SENSOR MOUNTED ON A MICROCONTROLLER PLATFORM (Nativa, 2023)
Nowadays, the global water crisis poses a great challenge to humanity and a risk to be managed by future generations. In order to use this resource consciously, it is known in the area of agricultural irrigation the need to evaluate the amount of water to be used. Among the soil moisture content determination methods, sensors, coupled to a programmable logic controller, emerge as an alternative to conventional laboratory methods, making the procedure faster and less labor intensive. In this sense, the present work aimed to evaluate the reliability and precision of a low-cost sensor to determine soil moisture content. It was concluded that the evaluated sensors did not present a known precision to estimate the level of soil moisture content. A FC-28 sensor coupled with a Arduino platform was used with three different soils (texture: low, medium and heavy), moisture ranging from 15 to 50%. The results indicated that soil texture influenced the readings, even at the same humidity. In addition, the evaluated sensors did not present replicability nor accuracy for less them 10% moisture differences. Therefore, there is need to calibrate each sensor individually.Keywords: arduino; irrigation; embedded systems. Análise de confiabilidade e calibração do sensor de umidade do solo FC-28 montado em plataforma microcontroladora RESUMO: Atualmente, a crise hídrica mundial representa um grande desafio à humanidade e um risco a ser gerenciado pelas gerações futuras. De forma a utilizar este recurso de forma consciente, estudos na área de irrigação agrícola apontam a necessidade de se estimar com precisão a quantidade de água a ser usada. Dentre os métodos de determinação da umidade do solo, os sensores, acoplados a um controlador lógico programável, surgem como uma alternativa aos métodos convencionais de laboratório, tornando o procedimento mais rápido e menos trabalhoso. Neste sentido, o presente trabalho avaliou a confiabilidade e precisão de um sensor de baixo custo para determinação da umidade do solo. Um sensor FC-28 associado à uma plataforma Arduino foi usado em três tipos diferentes de solos (texturas: leve, média e pesada), umidades variando de 15 a 50%. Concluiu-se que os sensores avaliados não apresentaram boa precisão para estimar o grau de umidade dos solos. A textura do solo influenciou diretamente as leituras dos sensores, mesmo para a mesma umidade. Além de não apresentaram replicabilidade nem precisão para diferenças menores de 15% nos valores de umidades. Portanto, é necessário calibrar cada sensor individualmente.Palavras-chave: arduino; irrigação; plataformas embarcadas.